Relationship between Selected Motivational Factors and the Performance of Public Secondary School Agriculture Teacher’s in Imenti South District, Kenya - Kirimi, Florence K. (Egerton University, 2013)
Teacher motivation is very important as it directly affects the students’ performance. The performance of agriculture teachers in Imenti South District has been low compared to other districts. This has been characterized by a decline in the agriculture subject results. This might have been contributed by inadequate teacher motivation. The purpose of this study was to determine the relationship between selected motivational factors and the performance of secondary school agriculture teachers in the district. The study used a cross-sectional research design. The target population comprised of all the head teachers and agriculture teachers of secondary schools in Imenti South District. Fifty-nine head teachers and fifty-nine agriculture teachers were randomly sampled from 70 schools in the District. A structured questionnaire was used by the researcher to collect data from the respondents. The reliability of the instrument was estimated using Cronbach’s Alpha Coefficient. Data was analyzed with the help of Statistical Packages for Social Sciences (SPSS). Descriptive statistics specifically frequencies and percentages, and inferential statistics particularly Pearson’s Product Moment Correlation were applied in data analysis. The hypotheses were tested at a 0.01 confidence level. The general working conditions in secondary schools were fair as noted by 69% of the respondents. The results also indicate that there is a positive correlation (0.444) between working condition and performance of agriculture teachers. The results also indicate that the teaching load of most teachers (59%) was moderate; however, they had been assigned other non-teaching roles. Further, the study revealed a negative correlation (-0.416) between teaching load and performance of agriculture. A correlation analysis between interpersonal relations and performance of agriculture teachers revealed a positive correlation of 0.403 and a pvalue of 0.01. The overall performance of agriculture teachers in the District has been fair for the last three years; however, this can be improved by reducing the teachers teaching load, improving the working conditions and interpersonal relations in the schools. The study recommends that agriculture teachers should make use of the surrounding community in the teaching of agriculture. Also, the school administrators should equip the available workshops with appropriate tools and equipment and in schools without workshops; the administrators should construct them and equip them appropriately to facilitate effective teaching.
A Thesis Submitted to the Graduate School in Partial Fulfillment of the Requirement for the Award of the Degree of Master of Science in Agricultural Education of Egerton University